Atto d'Amore - Hayes, Alfred 1911-1985; Shaw, Irwin 1913-1984; Douglas, Kirk 1916-2020; Robin, Dany 1927-1995; Laage, Barbara 1920-1988; Hayes, Alfred (A&R Productions, 2019)
An American soldier and a young French woman fall in love in Paris during World War II--Time: 1944
Original: USA 1954
s/w, Bildformat: 4:3 (1.33:1)
Keywords: Feature films; Romance films; War films; War / Feature; Romance / Feature; Film; DVD-Video